Deblur Capsule Networks - Santos, Daniel Felipe S. [UNESP]; Pires, Rafael G. [UNESP]; Papa, João P. [UNESP] (Springer Nature, 2024)
Blur is often caused by physical limitations of the image acquisition sensor or by unsuitable environmental conditions. Blind image deblurring recovers the underlying sharp image from its blurry counterpart without further knowledge regarding the blur kernel or the sharp image itself. Traditional deconvolution filters are highly dependent on specific kernels or prior knowledge to guide the deblurring process. This work proposes an end-to-end deep learning approach to address blind image deconvolution in three stages: (i) it first predicts the blur type, (ii) then it deconvolves the blurry image by the identified and reconstructed blur kernel, and (iii) it deep regularizes the output image. Our proposed approach, called Deblur Capsule Networks, explores the capsule structure in the context of image deblurring. Such a versatile structure showed promising results for synthetic uniform camera motion and multi-domain blind deblur of general-purpose and remote sensing image datasets compared to some state-of-the-art techniques.
Keywords: Capsules; Deblurring; Remote Sensing